Family caregiver’s burden in caring for stroke patients at Hospital Universiti Sains Malaysia (Hospital USM) - Rahman, Siti Noradni Ab (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Stroke is one of the chronic diseases that contributed to disabilities in many countries. Majority of stroke patients depend on their family for optimum recovery and survivor. The objective of this study was to measure the level of burden among family caregivers in caring for stroke patients at Hospital Universiti Sains Malaysia (Hospital USM). The socio demographic data of caregivers was assessed as the association factor for the level of burden among family caregivers. This study was a cross sectional study and Caregiver Identity theory was used in this study. The Zarit Burden Interview 12 questions short version Malay version questionnaire was used to measure the level of burden among 58 respondents from family caregivers of stroke patients in ward 2 Intan, 3 Utara, 7 Selatan and 7 Utara and also Rehabilitation Unit Hospital USM. The result showed that 93.1% of family caregiver for low burden whereas only 6.9% for high burden. Therefore, the level of burden among family caregiver is in low burden. There are no significant association between selected socio demographic data and level of burden among family caregiver who caring for stroke patient at Hospital USM. The age, gender, ethnicity, marital status, education level, occupation, family income and relationship to patient of 58 caregivers did not show any significant statistical difference in relation to their perceived burden.